A nationwide survey on producer and veterinarian perceptions of the painfulness of procedures and disease states in dairy and beef cattle - Edwards-Callaway, Lily N.; Keller, Kayleigh P.; Oselinsky, Katrina; Johnstone, Elizabeth; Cramer, Catie; Román-Muñiz, Noa; Stallones, Lorann; Coetzee, Johann F. (Frontiers in Pain Research, 2023)
Failure to adequately manage pain in cattle causes suffering and is thus a welfare concern for the livestock industry. The objectives of this study were to summarize caregiver perceptions of the painfulness of various procedures and disease conditions in cattle. This survey also assessed factors that impact the perception of painfulness and determined relationships between pain perception and mitigation in producers and veterinarians in the United States beef and dairy cattle industries. An online survey was distributed via organization listservs (FarmProgress master file, American Association of Bovine Practitioners, Academy of Veterinary Consultants, National Milk Producers Federation Farm Evaluators) and social media groups Dairy Moms and Dairy Girl Network Facebook group) representing beef and dairy veterinarians and producers. The survey included questions about respondent demographics and pain perception and frequency of pain mitigation use for a variety of common husbandry procedures and disease conditions in cattle less than 2 months, 2 to 12 months, and greater than 12 months of age. Descriptive statistics were generated, and ordinal logistic regressions were used to assess the relationship between perceived pain level, frequency of pain mitigation use, and respondent demographic factors (e.g., gender, age, and role). Although limited, some respondents perceived that there was “no pain” associated with the listed procedures and conditions. Across the majority of procedures and conditions and cattle age categories, men perceived procedures to be less painful than women (P < 0.05). Veterinarians and producer-veterinarians perceived procedures to be more painful than producers (P < 0.05) for the majority of procedures and conditions. There were differences identified between respondent age groups in pain perception but the trends were not consistent across procedures and conditions. There was a positive linear trend, with greater perceived pain associated with greater likelihood of providing local and systemic analgesia for all procedures and conditions across all cattle age categories (P ≤ 0.02). Perception of pain is complex and multifactorial, and it influences the likelihood to treat pain in cattle. This research highlighted the importance of understanding how these factors may play a role in increasing the use of pain mitigation within the cattle industries.